1986
DOI: 10.1148/radiology.158.2.3941861
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma evaluation with CT: preoperative staging and detection of postoperative recurrence.

Abstract: CT was performed prior to surgery in 103 patients with colorectal carcinoma to assess its value in staging the tumor. Preoperative IBD scans had sensitivities and specificities of 72.7% and 98.9% in detection of liver metastases, 25.9% and 96% in detection of lymph node metastases, and 61.2% and 80.6% in detection of local extension. Compared with the Duke's classification, CT correctly staged only 47.5% of patients: 16.6% were upstaged, and 83.3% were downstaged. Recurrent tumors developed in 11 of 67 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
87
2
6

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(99 citation statements)
references
References 0 publications
4
87
2
6
Order By: Relevance
“…The overall accuracy of T-stage prediction by each of our observers was 60.3 and 60.8% compared with histology, whereas identification of T3/T4 tumours was 85.9 -92.4% sensitive, with a PPV of at least 90 -92%. These results appear to compare favourably with other studies, which have reported sensitivities of between 55 and 61% and specificities of 67 -81% in the detection of 'serosal', 'extramural' or 'local (T3 -T4) invasion (Freeny et al, 1986;Acunas et al, 1990;Zerhouni et al, 1996). However, this relative lack of definition of depth of invasion makes direct comparison between those studies and our own results difficult.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The overall accuracy of T-stage prediction by each of our observers was 60.3 and 60.8% compared with histology, whereas identification of T3/T4 tumours was 85.9 -92.4% sensitive, with a PPV of at least 90 -92%. These results appear to compare favourably with other studies, which have reported sensitivities of between 55 and 61% and specificities of 67 -81% in the detection of 'serosal', 'extramural' or 'local (T3 -T4) invasion (Freeny et al, 1986;Acunas et al, 1990;Zerhouni et al, 1996). However, this relative lack of definition of depth of invasion makes direct comparison between those studies and our own results difficult.…”
Section: Discussionsupporting
confidence: 83%
“…The reported sensitivities for lymph node detection range between 19 and 97% (Freeny et al, 1986;Acunas et al, 1990;Zerhouni et al, 1996;McAndrew and Saba, 1999;Laghi et al, 2002). Inter-observer agreement ¼ 79% (k ¼ 0.59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite several articles reporting TRUS as the most accurate imaging method for the local staging of rectal tumors [2][3][4], a recent article [5] reported a trend toward overstaging the degree of tumor penetration within the bowel wall. The reported accuracy of CT has been variable, depending on patient selection (early or advanced neoplasia) and, most importantly, on the technical conditions of the examination (presence or absence of rectal distention) [6][7][8][9][10][11]. The purpose of our study was twofold: to compare the results of CT performed with a simultaneous water enema technique (WE-CT) with those of TRUS for the local staging of low colorectal tumors and to define which criteria is more useful in CT detection of metastatic local lymph node involvement.…”
mentioning
confidence: 99%